Summer paleohydrology during the Late Glacial and Early Holocene based on δ2H and δ18O from Bichlersee, Bavaria. ... - Prochnow, Maximilian; Strobel, Paul; Bliedtner, Marcel; Struck, Julian; Bittner, Lucas; Szidat, Sönke; Salazar, Gary; Schneider, Heike; Acharya, Sudip; Zech, Michael; Zech, Roland (Nature Publishing Group, 2023)
Isotope-based records provide valuable information on past climate changes. However, it is not always trivial to disentangle past changes in the isotopic composition of precipitation from possible changes in evaporative enrichment, and seasonality may need to be considered. Here, we analyzed δ2H on n-alkanes and δ18O on hemicellulose sugars in sediments from Bichlersee, Bavaria, covering the Late Glacial and Early Holocene. Our δ2Hn-C31 record documents past changes in the isotopic composition of summer precipitation and roughly shows the isotope pattern known from Greenland. Both records show lower values during the Younger Dryas, but at Bichlersee the signal is less pronounced, corroborating earlier suggestions that the Younger Dryas was mainly a winter phenomenon and less extreme during summer. δ18Ofucose records the isotopic composition of the lake water during summer and is sensitive to evaporative enrichment. Coupling δ2Hn-C31 and δ18Ofucose allows calculating lake water deuterium-excess and thus ...